Programación radial para las personas de tercera edad en la ciudad de Latacunga. - Martínez Merchán, María Lorena (2018)
The different means of communication, including radio, do not accommodate older adults, despite the fact that the Organic Law of Communication, together with the Constitution of Ecuador, mention in their articles the implementation of programs related to the good living of all the groups of the community, in the local radio has not yet been demonstrated this type of programming. The project investigated this problem in the city of Latacunga, which allowed designing a proposal that contributes to the solution of the problem. The technical scientific foundation is composed of concepts and theories based on bibliographic sources, among them, mention is made of participatory communication, which today is of vital importance for the individual. To carry out the project research methods were applied how the quantitative method that allowed the collection of statistical data, making use of the survey as well as the qualitative method was used, using the interview technique, which was used to different managers of radios from Latacunga city data that served to perform an analysis of the situation, with the execution of the interviews it was possible to verify the void that exists in the radio of a program for the older adults while with the application of the surveys it was possible to carry out the tabulation and obtain the results, which determined the interest that the adults have for the local radio and their agreement in the creation of a specific radio program where they are the main characters and diffusers of active and healthy aging.